2020
DOI: 10.3390/nano10030467
|View full text |Cite
|
Sign up to set email alerts
|

Core–Shell Structured Phenolic Polymer@TiO2 Nanosphere with Enhanced Visible-Light Photocatalytic Efficiency

Abstract: Core–shell structured TiO2 is a promising solution to promote the photocatalytic effectiveness in visible light. Compared to metal or semiconductor materials, polymers are rarely used as the core materials for fabricating core–shell TiO2 materials. A novel core–shell structured polymer@TiO2 was developed by using phenolic polymer (PP) colloid nanoparticles as the core material. The PP nanoparticles were synthesized by an enzyme-catalyzed polymerization in water. A subsequent sol–gel and hydrothermal reaction w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The chemical structures of the TiNPs/PSF-0.40, PSF and TiO 2 were characterized by FTIR spectroscopy. As shown in Figure 2 d, the broad absorption band from 3400 to 3200 cm −1 and the weak peak at 1616.3 cm −1 in the spectrum of the P25 TiO 2 are attributed to the stretching vibration of hydroxyl groups (OH) and absorbed water on the surface [ 20 ]. The FTIR spectra of the peaks situated at 1150 cm −1 , 1242 cm −1 , and 2967 cm −1 can be assigned to the −SO 2 stretch, C−O−C linkage, and aliphatic C−H stretch, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical structures of the TiNPs/PSF-0.40, PSF and TiO 2 were characterized by FTIR spectroscopy. As shown in Figure 2 d, the broad absorption band from 3400 to 3200 cm −1 and the weak peak at 1616.3 cm −1 in the spectrum of the P25 TiO 2 are attributed to the stretching vibration of hydroxyl groups (OH) and absorbed water on the surface [ 20 ]. The FTIR spectra of the peaks situated at 1150 cm −1 , 1242 cm −1 , and 2967 cm −1 can be assigned to the −SO 2 stretch, C−O−C linkage, and aliphatic C−H stretch, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Neghi et al prepared polyvinyl alcohol/chitosan-TiO 2 composite applied for photocatalytic removal of metronidazole under UV-light [ 19 ]. Xu et al prepared the Phenolic Polymer@TiO 2 composite to degrade rhodamine B [ 20 ]. Mahmoud et al compared the use of suspended and attached catalysts for degradation of 2, 4-dichlorophenol (2, 4-DCP), and found that suspended catalyst showed faster degradation rate than attached catalyst due to better interaction between catalyst particles and pollutant molecules [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Along with this major challenge, the morphology of the resulting material is usually core-shell: the outer shell is an organic polymer, whereas the inner core is an inorganic semiconductor (TiO 2 ). In this core-shell form, [31][32][33][34] the photo-excited electrons from organic polymers are not effectively harvested because generated excitons are confined to the inorganic semiconductor core. [35,36] An outer polymer shell makes the photocatalyst more hydrophobic, leading to a decrease in the HER performance because of the difficult access to water.…”
Section: Introductionmentioning
confidence: 99%